Bank Mergers and the Human Factor: Organizational Culture’s Influence on Employee Job Satisfaction (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study explores the impact of organizational culture on job satisfaction from the employees’ perspective in merged public sector banks (PSBs) in India. In light of the recent wave of banking mergers undertaken to promote financial consolidation and operational efficiency, the human resource implications, particularly the role of cultural integration in shaping employee satisfaction, remain insufficiently addressed. Drawing on responses from a structured survey of 420 employees across various merged PSBs, the research employs descriptive statistics, correlation, and regression analyses to investigate the relationship between perceived organizational culture and job satisfaction. The findings reveal a statistically significant yet negative correlation, indicating that despite advancements in structural integration, cultural misalignment may be undermining employee satisfaction. These results highlight the critical need for culturally sensitive integration strategies to ensure that the broader objectives of the merger are effectively realised at the human capital level.